2022
DOI: 10.3389/fnbeh.2022.834880
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Resilience to Predator Stress-Enhanced Ethanol Drinking Is Associated With Sex-Dependent Differences in Stress-Regulating Systems

Abstract: Stress can increase ethanol drinking, and evidence confirms an association between post-traumatic stress disorder (PTSD) and the development of alcohol use disorder (AUD). Exposure to predator odor is considered a traumatic stressor, and predator stress (PS) has been used extensively as an animal model of PTSD. Our prior work determined that repeated exposure to intermittent PS significantly increased anxiety-related behavior, corticosterone levels, and neuronal activation in the hippocampus and prefrontal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In mice, repeated exposure to dirty rat bedding can also be used to subgroup rats into “sensitive” and “resilient” phenotypes based on percent change in ethanol drinking before and after repeated stressor exposure ( Alavi et al, 2022 ). Mice that show approximately 20% increase in home cage alcohol drinking after the stressor exposure compared to baseline drinking are defined as “sensitive”, while “resilient” mice show decreased or no change in drinking after the stressor ( Alavi et al, 2022 ). This method to examine individual differences focuses on drinking behavior rather than behavioral coping strategies during the stressor such as avoidance or immobility.…”
Section: Stress Reactivity: Individual Differences and Implications F...mentioning
confidence: 99%
See 3 more Smart Citations
“…In mice, repeated exposure to dirty rat bedding can also be used to subgroup rats into “sensitive” and “resilient” phenotypes based on percent change in ethanol drinking before and after repeated stressor exposure ( Alavi et al, 2022 ). Mice that show approximately 20% increase in home cage alcohol drinking after the stressor exposure compared to baseline drinking are defined as “sensitive”, while “resilient” mice show decreased or no change in drinking after the stressor ( Alavi et al, 2022 ). This method to examine individual differences focuses on drinking behavior rather than behavioral coping strategies during the stressor such as avoidance or immobility.…”
Section: Stress Reactivity: Individual Differences and Implications F...mentioning
confidence: 99%
“…Exposure to a predator odor stressor has been shown to be a valid and reliable animal model to examine symptom profiles of PTSD. For example, predator odor models can induce PTSD phenotypes including hyperarousal ( Blount et al, 2023 ; Schwendt et al, 2018 ), avoidance behavior ( Edwards et al, 2013 ; Weera et al, 2020 ; Albrechet-Souza et al, 2020 ; Albrechet-Souza and Gilpin, 2019 ; Brodnik et al, 2017 , 2020 ), contextual stress memory ( Ornelas et al, 2021a , 2021b ; Tyler et al, 2020 ) and increases in plasma corticosterone levels ( Ornelas et al, 2021a ; Alavi et al, 2022 ; Finn et al, 2018 ; Cozzoli et al, 2014 ), indicative of changes in hypothalamic-pituitary-adrenal (HPA) axis activity. The HPA axis is the primary neuroendocrine system that regulates physiological and behavioral responses to stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predator odor stressor exposure can also be used to investigate the complex interaction between increased alcohol consumption and stress, which may help in understanding the neurobiology associated with comorbid PTSD and alcohol use disorder (Ornelas, Tyler, et al, 2021; Weera et al, 2020). For example, several studies have shown increased alcohol drinking (Alavi et al, 2022; Albrechet-Souza, Schratz, & Gilpin, 2020; Makhijani, Franklin, Van Voorhies, Fortino, & Besheer, 2021) or alcohol relapse-like behavior (Becker, Lopez, King, & Griffin, 2023; King & Becker, 2019) following exposure to varying predator odor stressors, including TMT. Importantly, not all individuals who experience a traumatic event develop PTSD.…”
Section: Introductionmentioning
confidence: 99%